ANALISIS PENGARUH TINGKAT PARTISIPASI DAN AKTUALISASI DIRI DOSEN PEREMPUAN UIN SUSKA RIAU TERHADAP PRODUKTIVITAS KERJA - Susnaningsih Mu’at (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
This research discusses the influence of woman lecturer’s participation and actualitation toward her job productivity. Research done by distributing the questionnaire in to 8 faculties in UIN Suska Riau. Based on the statistical test, it is known that by parsial, the actualisation and job participation has a positif effect but it is not significant toward productivity. Considering the small influence on the both variable which have been specified previously, hence, the early research model is modified ( model 1) by adding estimated variable which also influence productivity like the year of service and the fungional position. The result of the statistical test indicates that the functional position has positive and significant influence to job productivity.'The self actualisation also has a positive influence, but it is not significant. While the job participation and the year of service have a negative influence and there is no significant. The result of statistical test indicates simultanly that the fourth of free varibels, self actualisation, job participation, year of service, and functional position has significant influence to job productivity